Enabling High and Stable Electrocatalytic Activity of Iron‐Based Perovskite Oxides for Water Splitting by Combined Bulk Doping and Morphology Designing. Issue 1 (28th November 2018) - Dai, Jie; Zhu, Yinlong; Zhong, Yijun; Miao, Jie; Lin, Bowen; Zhou, Wei; Shao, Zongping
Abstract: The catalysts for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) are crucial for water splitting technology, and perovskite oxides have received tremendous attention as promising candidates due to the compositional flexibility and rich properties. Here, reported is the successful deployment of cost‐effective iron‐based perovskites into efficient water splitting catalysts with both high activity and stability by combined bulk and morphology tuning strategy. Through constructing 3D ordered macroporous (3DOM) structure of LaFeO3 perovskite, approximately twofold and approximately fourfold enhancement in activity for OER and HER, respectively were realized together with much improved OER durability. By a small amount of cobalt doping, both catalytic activity and stability were further improved with activity comparing favorably to or even outperforming Co‐/Ni‐rich perovskite catalysts. Enhanced performance is correlated with optimized Fe/O species, high surface area, and good charge/mass transport. Abstract : By combining the unique 3D ordered macroporous architecture and bulk doping, the enhanced oxygen evolution reaction (OER) and hydrogen evolution reaction activity and stability, especially OER stability, could be realized in Fe‐based perovskites, which originate from the optimized Fe/O species, high surface area, and good charge/mass transport.